2015
DOI: 10.1093/pcp/pcv014
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and ZmCCaMK are involved in brassinosteroid-induced antioxidant defense in maize leaves

Abstract: Brassinosteroids (BRs) have been shown to enhance stress tolerance by inducing antioxidant defense systems. However, the mechanisms of BR-induced antioxidant defense in plants remain to be determined. In this study, the role of calcium (Ca(2+)) and maize calcium/calmodulin-dependent protein kinase (CCaMK), ZmCCaMK, in BR-induced antioxidant defense, and the relationship between ZmCCaMK and Ca(2+) in BR signaling were investigated. BR treatment led to a significant increase in cytosolic Ca(2+) concentration in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(24 citation statements)
references
References 63 publications
0
24
0
Order By: Relevance
“…Cytosolic calcium concentration was measured by the calcium fluorescent probe Fluo-3/AM (Molecular Probes) based on the method of Yan et al ( 2015 ) and Zhang et al ( 1998 ). Briefly, 1 mM Fluo-3/AM in anhydrous DMSO (5 μL) was added to radish mesophyll protoplasts.…”
Section: Methodsmentioning
confidence: 99%
“…Cytosolic calcium concentration was measured by the calcium fluorescent probe Fluo-3/AM (Molecular Probes) based on the method of Yan et al ( 2015 ) and Zhang et al ( 1998 ). Briefly, 1 mM Fluo-3/AM in anhydrous DMSO (5 μL) was added to radish mesophyll protoplasts.…”
Section: Methodsmentioning
confidence: 99%
“…Further study founded that a 65 kDa microtubule-associated protein (MAP65), ZmMAP65-1a, directly phosphorylated by ZmMPK5, is required for BR-induced antioxidant defense ( Zhu et al, 2013b ). Recently, Ca 2+ and maize CCaMK gene, ZmCCaMK , was demonstrated to be required for BR-induced antioxidant defense ( Yan et al, 2015 ).…”
Section: Regulation Of Antioxidative System In Crop Plantsmentioning
confidence: 99%
“…In a recent study, BR treatment was unable to elicit antioxidant defense in the rice and maize CALCIUM/CALMODULIN-DEPENDENT PROTEIN KINASE (CCaMK) mutants. It was found that BR application results in increase in cytosolic Ca (2+) concentration followed by increase in activity of CCaMK which further enhanced the BR-induced increase in cytosolic Ca (2+) concentration thus forming a positive feedback loop of Ca (2+) and CCaMK in BR signaling ( Yan et al, 2015 ). ABA has also been demonstrated to be intricately involved in BR-orchestrated antioxidant defense via ZmMAP65-1a as inhibition of ABA biosynthesis reduces the expression and activity of ZmMAP65-1a ( Zhu et al, 2015 ).…”
Section: Role Of Brs At Physiological and Biochemical Levelmentioning
confidence: 99%